Znaczenie faktoringu dla polityki kredytowej przedsiębiorstwa - Zawadzka, Danuta (The Importance of Factoring for Companies' Credit Policy, 2007)
The paper concentrates on the factoring issue in companies' current financing. It consists of three parts. In the first one there is shown the essence of mutual crediting through companies in commercial transactions. The increase of the importance of trade credit can be observed in economic practice, especially through small companies, which have limited possibilities of getting funds from financial institutions. In the second part of the paper, there is shown the comparison between the banking and factoring services. They are recognized as the alternative forms of current financing. In the third part of the paper, the motives of factoring usage for amount due financing are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 676-682